СІМíЯ ПРАВОСЛАВНОГО СВЯЩЕННОСЛУЖИТЕЛЯ В 20ñ30-х рр. ХХ ст.: СОЦІАЛЬНО-ПРАВОВИЙ АСПЕКТ (Zaporizhzhia Historical Review, 2021)
In the article the position of members of family of orthodox priest in a period of changes of the sociopolitical system and destruction of traditional spiritual values is analyzed. The terms of labour activity of members of family of clergy and education of the children of clergy are characterized. Factors which influenced on using civil laws of the members of family of clergy during 1920ñ30-s defined. The dynamics of ousting of members of family from educational establishments, from public institutions during 1920ñ30-s.